A Review of the experimental studies of the cyclic behaviour of granular materials: Geotechnical and pavement engineering - Sabbar, A.; Chegenizadeh, Amin; Nikraz, Hamid (Australian Geomechanics Journal, 2016)
The cyclic behaviour of granular materials has become a critical issue in many civil engineering applications, especially in seismic hazard areas, offshore projects and pavements. Cyclic loading has a detrimental effect on the soil layers under foundations of buildings because it can generate unacceptable deformations and excess pore water pressure in these soil layers. This paper presents the results of research on the behaviour of granular materials under cyclic loading in geotechnical engineering. The cyclic behaviour of granular materials is investigated by using different testing devices as well as various testing conditions. Also, this paper provides a comparison between the response of granular materials in geotechnical aspect under cyclic and monotonic loadings. Moreover, the influence of factors such as drainage conditions, sample preparation method, confining pressure, relative density, frequency, loading type, and stress level on the cyclic behaviour of granular materials was reviewed.